Is It Time to Start Worrying? A Comprehensive Report on the Three-Year Prevalence of ESBL-Producing Bacteria and Their Trends in Antibiotic Resistance from the Largest University Hospital in Slovakia - Yashar Jalali; Andrea Kološová; Adriána Liptáková; Ján Kyselovič; Anna Oleárová; Monika Jalali; Juraj Payer (MDPI AG, 2024)
Background/Objectives: Over the past few decades, extended-spectrum β-lactamase (ESBL)-producing bacteria have become a great concern in healthcare systems worldwide, imposing large burdens by increasing antimicrobial resistance and patient morbidity. Given the high mortality rates and emergence of multidrug-resistant (MDR) strains, monitoring ESBL prevalence and resistance patterns is crucial. This study aimed to evaluate ESBL-producing Escherichia coli, Proteus mirabilis, and Klebsiella pneumoniae over three years, focusing on phenotypic distribution and resistance profiles. Methods: A total of 1599 ESBL-producing bacterial samples were collected and analysed. A panel of 20 antibiotics was tested to determine resistance traits. Data were recorded on phenotypical distribution, isolation types, changes in antibiotic resistance, and the relation of such changes to antibiotic consumption (defined daily dose) from clinical isolates. Results: Phenotypical analysis revealed the minimal presence of the Cefotaximase from Munich (CTX-M) phenotype in E. coli and K. pneumoniae, creating a distinct epidemiological profile compared to global patterns. Shifts in isolation trends, particularly in P. mirabilis, suggest an expected increase in associated-mortality-rate in the coming years. While resistance trends were not statistically significant, MDR and extensively drug-resistant (XDR) strains were identified across all three bacteria. Only meropenem showed consistent 100% efficacy against E. coli, with other antibiotics displaying only partial effectiveness. Conclusions: These findings highlight the need for ongoing surveillance of ESBL-producing bacteria and underscore challenges in managing antibiotic resistance due to limited efficacy of last-resort treatments. The unique phenotypical distribution observed could impact local resistance management strategies in hospital settings in the coming years.